Morphological and molecular characteristics of Angiostrongylus cantonensis Chen et al., 1935 from Bac Ninh and Hung Yen provinces, Vietnam - Hien, Hoang Van; Doanh, Pham Ngoc; Dung, Bui Thi; Duc, Nguyen Van (Academia Journal of Biology, 2014)
The rat lungworm, Angiostrongylus cantonensis, is a nematode that parasites the lungs of rats - the natural definitive hosts of the nematodes. This nematode can cause Angiostrongyliasis for human when people eat uncooked/undercooked snails infected with infective larvae (L3). In Vietnam, although some suspected Angiostrongyliasis cases have been reported, there has been no investigation for A. cantonensis in natural definitive hosts (rats). This is the first record of A. cantonensis in rats collected from Bac Ninh and Hung Yen provinces, Vietnam based on morphological and molecular identification. A total of 234 rats, including 147 R. norvegicus and 87 R. losea, were examined. The rat lungworms were found in both rat species. The overall infection rates in Hung Yen and Bac Ninh provinces were 40.4% and 21.4%, respectively. The infection rates in R. norvegicus (60.0 and 26.3%) were higher than that of R. losea (14.4% and 2.2%). The description of A. cantonensis and the molecular phylogenetic relationship among Angiostrongylus genus were given and discussed herein.